PENGARUH KINERJA KEUANGAN, SIZE DAN REPUTASI KAP TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Yuliana, Yuliana; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to find out the influenceof financial performance, firm size, and the reputation ofPublic Accountant Officethat affect timelinessof the submission of financial statements at manufacturingcompanies which are listed in Indonesia Stock Exchange in 2011-2013 periods. The research samples has beenselected by using purposive sampling technique so 113 companies (339 firm years) which have meet the criteriahave been selected as samples. The data in this research is the secondary data. The data analysis technique hasbeen done by using logistic regresions analysis with the significance level is 5% and SPSS 16 version program.Based on the result of logistic regressions analysis in this research shows that current ratio, return on asset, andfirm size do not have any positive influence to the timelinessof the submission of financial statements meanwhilethe reputation of public accountant officehas positive influence to the timeliness of the submissionof financialstatements.Keywords: Financial Performance, Firm Size, the Reputation of Public Accountant Office, the Timeliness ofof the Submission of Financial Statements.